Cross-Sectional Analysis to Discover Phishing Cyberattack Trends in Saudi Arabia - Alarifi, Suaad; Aljeaid, Dania (Journal of Ecohumanism, 2025)
Phishing attacks exploit social engineering to deceive users, potentially leading to data breaches, financial losses, or, worse, identity theft. To counter these threats, Saudi Arabia has recently implemented robust initiatives, including awareness campaigns, regulatory measures, and new legislation aimed at phishing prevention. This cross-sectional study, as part of an ongoing longitudinal series, assesses the effectiveness of these efforts by comparing data from phishing identification surveys conducted in 2018 and 2022. The findings indicate a 632% increase in phishing attempts reported by Saudi users, accompanied by notable gains in user awareness and skepticism. However, the success rates of these attacks remain unclear, highlighting the need for continued assessment of user resilience. The study also identifies evolving phishing tactics, offering strategic insights to strengthen anti-phishing measures in Saudi Arabia and guide global efforts against similar threats.